Nomenclatural remarks on Iris orientalis (Iridaceae) and four related names including the Linnaean I. ochroleuca - Boltenkov, Eugeny V.; Güner Adi̇l (Phytotaxa, 2021)
Nomenclature issues of irises associated with the Turkish flora are discussed. In particular, Iris orientalis and four related names, I. ochroleuca, I. monnieri, I. gigantea, and I. albida, are typified. Lectotypes are designated for I. orientalis, I. monnieri, I. gigantea, and I. albida; a neotype for the Linnaean name I. ochroleuca is designated. Also, further support is provided for the suggestions that I. monnieri is a synonym to I. orientalis, and the author citation of the name I. monnieri is Redouté.